Mycotic Aneurysm of Aorta Following Mitral Valve Replacement A Case Report - Rahim, AMA; Zaman, MH; Hossain, GMM; Alam, SAN; Quashem, MA; Ahmed, NU; Mahmood, KN (Cardiovascular Journal, 2012)
The term mycotic aneurysm refers to aneurysm associated with infection by microorganism. Sir William Osler first coined the term mycotic aneurysm in 1885 by disclosing the relation between abnormal cardiac valves and infection with micrococci not with fungi. An 11 years old female from Feni presented with asymptomatic vascular swelling in abdomen referred by a cardiologist. CT angiogram revealed fusiform aneurysm in distal part of abdominal aorta involving ostioproximal part of both common iliac arteries and saccular aneurysm of distal part of superior mesenteric arteries suggestive of mycotic aneurysm. Patient underwent vascular operation aorto biilliac bypass by PTFE graft with excision and ligation of aneurysm of superior mesenteric arteries. Mycotic aneurysm in bacterial endocarditis is rare. It is a challenging job for the cardiologists, infectious disease specialists and vascular surgeon. Time appropriate skilled prompt surgical management can bring smile for both patients and physicians. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12281 Cardiovasc. j. 2012; 5(1): 107-111